EPISIOTOMY TO RELIEVE DYSTOCIA DUE TO INFANTILE VULVA IN A GOAT - HEMALATHA, H; MURUGAVEL, K; ANTOINE, D; KANTHARAJ, S; RAJU, M S (The Indian Journal of Animal Reproduction, 2017)
A full term pregnant two-year-old non-descript nulliparous she goat was presented with the history of unproductive straining since 6h. Gynaeco-clinical examination revealed the case of dystocia due to infantile vulva. Episiotomy operation was performed and a live male kid was removed per-vagium,